Sistem Informasi Pelayanan Aduan Persampahan dan Lingkungan Hidup Kota Magelang Berbasis Website - Hery Setiawan; Maimunah; Pristi Sukmasetya (STMIK Budi Darma, 2023)
Complaints have a very important role in creating comfort and safety in an effort to build awareness in waste management in Magelang City. It involves various parties, ranging from the government, the community, to the private sector. Although the Magelang City Environmental Agency is responsible for the implementation of service functions related to waste management and the environment, its implementation has not reached an optimal level due to constraints from the current service mechanism. The media used to submit complaints is still ineffective, thus hampering the communication process between the people who complain about the problem and the officers who follow up on the complaint. The system development method applied is the Lean Software Development method. This research aims to build a complaint management system related to waste in order to overcome the challenges faced today. This system is built in the form of a web and uses the PHP programming language and applies the MySQL database, while also using Unified Modeling Language (UML) modeling. This system is expected to contribute to improving the effectiveness of waste and environment-related complaint management in Magelang City, making it easier for the community to submit complaints and officers can respond and follow up on reported problems more quickly, as well as strengthening efforts to build awareness of the importance of good waste management for environmental comfort and safety